DC Task Team Report - Hesla, Erling (IEEE transactions on industry applications, 2014)
In light of the rapid growth of dc loads, ICPS created a small team to outline design considerations for dc distribution and controls. Broad interest in the subject brought in a large group who provided substantial support for the Team. The report begins with a brief background followed by discussion of design considerations that affect ICPS and IAS. The key part of the report is Part IV, which outlines in detail a path forward for ICPS and for IAS. Appendix A outlines an approach toward developing dc standards or recommended practices for design of industrial and commercial power systems. Appendix B lists some of the organizations and individuals that are working on related dc issues at present.